Estratégias para minimizar os efeitos de um ambiente térmico adverso para frangos de corte - Oliveira, P. M. [UNESP]; Faria Júnior, M. J.A. [UNESP]; Garcia Neto, M. [UNESP] (FapUNIFESP (SciELO), 2016)
Heat limits the production of broilers. This study evaluated the interactions between early thermal conditioning (ETC) and the electrolyte balance (EB) on performance and characteristics of birds' carcass. Thus, the electrolyte balance (BE = Na+ + K+ - Cl-), was set to 350mEq/kg and electrolyte ratio (K+ + Cl-)/ Na+ in 3:1 by the PPFR program. The experiment was carried out at the Animal Science department of the Faculty of Veterinary Medicine of Araçatuba / UNESP. 240 1 day old Cobb-500 male chicks were used, lodged in metal batteries with 24 divisions and automatic electric heating. The experimental design was completely randomized in a 2x2 factorial arrangement, totaling 4 treatments with 6 replicates and 10 birds per experimental plot. ETC occurred on the 5th day of age for 24 hours at 36.5°C in half of the batch. Subsequently, these birds were transferred to an environmentally controlled shed and were grown in boxes, in the same way as the other half that had not received ETC treatment. The effects of chronic heat stress (6 hours at 32°C) applied from the 35th through the 39th day of age were evaluated. Temperature and air humidity, as well black-globe temperature were monitored electronically. Food and water were provided ad libitum. The growth performance data and the mortality rate of birds were measured. The results were subjected to analysis of variance and comparison of means was done by Tukey test. There were no interaction effects between ETC and EB on performance and characteristics of birds' carcass. The ETC and EB strategies proved to be ineffective to mitigate the effects of chronic heat stress in broilers.
Strategies to minimize the adverse thermal environment in broiler chickens
Keywords: Acid-base equilibrium; Birds; Early thermal conditioning; Electrolytes; Heat stress disorders